Mapping and Analysis of Hepatitis A Disease Distribution Based on Risk Factors in Bondowoso District - Hikmah, Faiqatul; Nuraini, Novita; Sari, Estu Pratika (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Hepatitis A is caused by the Hepatitis A virus (HAV). Bondowoso experienced an Extraordinary Occurrence HAV with 60 patients who were mostly teenagers. This study aimed to map and analyze the distribution of HAV based on risk factors in Bondowoso in 2016. This was descriptive research and application which was used to create digital map ArcView GIS 3.3. The result of this research was a map of HAV distribution and risk factor in Bondowoso. Mapping results showed that the risk factors cause HAV outbreak in Bondowoso were unhealthy living behaviors, Open Defecation, and rainfall intensity. The population density was not a risk factor due to outbreaks or extraordinary occurrences of hepatitis A occurred in areas of low population density. Suggestion for the Health Department to cooperate with an educational institution to increasing of clean and healthy behaviors Additionally, Hepatitis A immunization, and provide clean water.